2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318759
|View full text |Cite
|
Sign up to set email alerts
|

Towards decoding of functional movements from the same limb using EEG

Abstract: In recent years, there has been an increasing interest in using electroencephalographic (EEG) activity to close the loop between brain oscillations and movement to induce functional motor rehabilitation. Rehabilitation robots or exoskeletons have been controlled using EEG activity. However, all studies have used a 2-class or one-dimensional decoding scheme. In this study we investigated EEG decoding of 5 functional movements of the same limb towards an online scenario. Six healthy participants performed a thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…After deduplication, 330 studies underwent title and abstract screening. Forty six studies passed this stage and among these, 16 were removed after full-text screening due to the following reasons: insufficient EEG and robotic data [59][60][61][62][63][64][65], the study was out of scope [66][67][68], the study design was not for hand/finger movement [69][70][71][72], no robot or mechatronic device was involved in the study [73,74]. A final sample of 30 studies were included in the qualitative review.…”
Section: Search Resultsmentioning
confidence: 99%
“…After deduplication, 330 studies underwent title and abstract screening. Forty six studies passed this stage and among these, 16 were removed after full-text screening due to the following reasons: insufficient EEG and robotic data [59][60][61][62][63][64][65], the study was out of scope [66][67][68], the study design was not for hand/finger movement [69][70][71][72], no robot or mechatronic device was involved in the study [73,74]. A final sample of 30 studies were included in the qualitative review.…”
Section: Search Resultsmentioning
confidence: 99%
“…Lastly, unlike the methods of [48][49][50][51][52][53][54][55][56], the proposed method showed the potential to classify both real (executed) and imagined movements by applying estimation classifiers not only to one-dimensional functions (e.g., PSD), but relying on features extracted from structures of the TFDs, providing additional insights into the signal's characteristics. Contrary to the known methods for limb movement EEG classification and analysis, which are usually focused on responses of certain electrode channels (in [48,49], C3 and C4; in [50], F3, F4, C3, C4, P3, P4, O1, and O2; in [56] Fz, FC5, FC1, FCz, FC2, FC6, C3, Cz, C4, CP5, CP1, CP2, CP6, P3, Pz, and P4), in the proposed approach, valuable information is also obtained from electrodes that are usually neglected for this kind of estimation (F7, F8, and T4).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the known methods for limb movement EEG classification and analysis, which are usually focused on responses of certain electrode channels (in [48,49], C3 and C4; in [50], F3, F4, C3, C4, P3, P4, O1, and O2; in [56] Fz, FC5, FC1, FCz, FC2, FC6, C3, Cz, C4, CP5, CP1, CP2, CP6, P3, Pz, and P4), in the proposed approach, valuable information is also obtained from electrodes that are usually neglected for this kind of estimation (F7, F8, and T4). In light of this, the classification performance of the above-cited methods [48][49][50][51][52][53][54][55][56] could be upgraded and integrated into multi-criteria computer-based clinical decision-support systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After deduplication, 330 studies underwent title and abstract screening. Forty six studies passed this stage and among these, 16 were removed after full-text screening due to the following reasons: insufficient EEG and robotic data [44][45][46][47][48][49][50], the study was out of scope [51][52][53], the study design was not for hand/finger movement [54][55][56][57], no robot or mechatronic device was involved in the study [58,59]. A final list with 30 studies was identified as eligible for qualitative review.…”
Section: Figure 1 Study Selection Flowchartmentioning
confidence: 99%